Substantiation of Geometric Parameters of a Variable Inertia Moment Pulley - Kuropiatnyk, Olek. S.; Sharapov, M. Y. (Science and Transport Progress, 2023)
Purpose. The main purpose of our work is to substantiate the geometric parameters of a variable moment of inertia pulley, which can reduce the weight of a drive with such a pulley. Methodology. It was found that the masses of the pulley and support elements have the greatest influence on the weight of the drive, so we focused on the pulley. Improvement of the pulley design and determination of its rational geometric parameters were carried out in three stages. At the first stage, the size of the rim was reduced in accordance with the diameter of the rope. At the second stage, a multivariate calculation was performed for a pulley with spokes that expand toward the rim. Holes were made in the spokes to reduce the pulley weight. The fundamental difference of the pulley calculated at the third stage is the absence of holes in the spokes, which makes it possible to increase the rigidity of the structure. The control parameter was the angle of expansion of the spokes. The problem of establishing a rational value for this angle was solved using the SolidWorks computer program with the Simulation application, subject to the constraints on the safety factor (at least two) and the structural rigidity parameters (displacement along three coordinate axes and the resulting displacement at the level of the values for the base structure). Findings. It has been established that the weight optimization of a drive with a variable moment of inertia pulley is advisable to be carried out by reducing the masses of the pulley and supporting elements. The best design is that of a variable moment of inertia pulley that contains spokes (without holes) that expand toward the rim; the rational angle of expansion of the spokes is 25°. If a pulley with reasonable geometric parameters is used, the mass of the drive will decrease by 16% in the case of a 33 % reduction in the mass of the pulley itself compared to the mass of the basic design. Originality. A new design is proposed and rational parameters of the variable moment of inertia pulley are substantiated, which make it possible to reduce the mass of the drive with such a pulley. Practical value. The use of the pulley of this design will reduce the load on the electric motor during startup, as well as the load on the supporting structures.